Digital Business Strategy in 3D Laser Startupreneur through the DAGMAR Framework - Muh Tahir; Nuke Puji Lestari Santoso; Fitra Putri Oganda; Syahrul Mu'Arif Wahid; Harry Agustian; Oliver Sauntos (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
Rapid development of digital technology requires startupreneurs to optimize marketing strategies to strengthen consumer loyalty, particularly in emerging industries such as 3D Laser services. This study aims to analyze the effect of DAGMAR based digital marketing, represented by Brand Awareness, Product Information Understanding, and Digital Content Attractiveness, on Product Interest and its implication for Purchase Loyalty in the 3D Laser startupreneur context. This research employed a quantitative approach using a survey method involving 100 respondents. The collected data were analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS) to examine the direct and indirect relationships among the research variables. The findings indicate that Brand Awareness, Product Information Understanding, and Digital Content Attractiveness have positive and significant effects on Product Interest. Furthermore, Product Interest has a positive and significant effect on Purchase Loyalty. The mediation test also confirms that Product Interest significantly mediates the relationship between the three independent variables and Purchase Loyalty. These results emphasize that Product Interest serves as a psychological mechanism connecting DAGMAR based digital marketing strategies with longterm consumer loyalty. Enhancing Brand Awareness helps consumers recognize and recall the brand, while Product Information Understanding supports informed decision making through clear and relevant product details. Digital Content Attractiveness captures attention and encourages engagement through visual and interactive content. Practically, startupreneurs in the 3D Laser industry should integrate data driven digital marketing strategies to build stronger consumer relationships, encourage repeat purchases, and foster positive word-of-mouth for sustainable business growth.